2017
DOI: 10.1111/1750-3841.13584
|View full text |Cite
|
Sign up to set email alerts
|

High Salinity Relaying to Reduce Vibrio parahaemolyticus and Vibrio vulnificus in Chesapeake Bay Oysters (Crassostrea virginica)

Abstract: Cases of Vibrio infections in the United States have tripled from 1996 to 2009 and these infections are most often associated with the consumption of seafood, particularly oysters (Crassostrea virginica). Information is needed on how to reduce numbers of Vibrio parahaemolyticus and Vibrio vulnificus in bi-valve molluscan shellfish (for example, oysters). The purpose of this study was to evaluate the effectiveness of high salinity relaying or treatment in recirculating aquaculture systems (RASs) as methods to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Our study showed no significant differences in the antimicrobial susceptibility profiles of V. vulnificus and V. parahaemolyticus isolated from the oysters before and during the relaying in both sites. This suggests that the salinity of the relaying sites did not impact the antimicrobial susceptibility profiles of the Vibrio isolates, although it reduced the overall concentration of these bacteria in oysters (26).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our study showed no significant differences in the antimicrobial susceptibility profiles of V. vulnificus and V. parahaemolyticus isolated from the oysters before and during the relaying in both sites. This suggests that the salinity of the relaying sites did not impact the antimicrobial susceptibility profiles of the Vibrio isolates, although it reduced the overall concentration of these bacteria in oysters (26).…”
Section: Discussionmentioning
confidence: 97%
“…At each selected time interval (days 0, 7, 14, and 21), 3 composites were collected from each relaying site. Collected oysters were analyzed for presumptive V. parahaemolyticus and V. vulnificus, and abundances were determined using the alkaline peptone water (APW) 3-tube MPN series (26).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations